Adapt: Why Success Always Starts with Failure - Harford, Tim (Abacus, 2012)
Everything we know about solving the world's problems is wrong. Out: P lans, experts and above all, leaders. In: Adapting - improvise rather than plan; fail, learn, and try againIn this groundbreaking new book, Tim Harford shows how the world's most complex and important problems - including terrorism, climate change, poverty, innovation, and the fi nancial crisis - can only be solved from the bottom up by rapid experi menting and adapting.From a spaceport in the Mojave Desert to the stre et battles of Iraq, from a blazing offshore drilling rig to everyday d ecisions in our business and personal lives, this is a handbook for su rviving - and prospering - in our complex and ever-shifting world.